Rhetorical Constellations and the Inventional/Intersectional Possibilities of #MeToo. (October 2019) - Bloomfield, Emma Frances
In this project, I analyze news coverage of the #MeToo movement to categorize how blame is assigned and what corrective actions are prescribed for the pervasive problem of sexual violence. Although it is tempting to scapegoat individuals, this practice often limits the scope of sexual violence to isolated cases. Transcendence is an alternative route to redemption that attributes blame to structural and societal forces. However, transcendence may erase intersectional differences and silence voices by overshadowing individual stories. I argue that the risks in focusing exclusively on either scapegoating or transcendence can be mediated through the lens of a rhetorical constellation. This approach calls for media and news coverage of #MeToo to attend to the specific circumstances of individual cases and to frame those unique people, voices, and stories as part of a series of interactions with other instances of sexual violence that constitute a call for societal change.